Draft Genome Sequence of Yellow Pigmented Jeotgalibacillus alimentarius JY-13 T , the First Halophile Strain of the Genus Jeotgalibacillus - Yaakop, A.S.; Chan, Kok Gan; Gan, H.M.; Goh, K.M. (American Society for Microbiology, 2015)
Jeotgalibacillus alimentarius JY-13T (=KCCM 80002T=JCM 10872T) is a moderate halophile. In 2001, this was the first strain of the newly proposed Jeotgalibacillus genus. The draft genome of J. alimentarius was found to consist of 32 contigs (N50, 315,125 bp) with a total size of 3,364,745 bp. This genome information will be helpful for studies on pigmentation as well as applications for this bacterium.